Therapeutic plasma exchange in steroid-refractory multiple sclerosis relapses. A retrospective two-center study. (January 2021) - Blechinger, Stephan; Ehler, Johannes; Bsteh, Gabriel; Winkelmann, Alexander; Leutmezer, Fritz; Meister, Stefanie; Santer, Agnes; Hecker, Michael; Berger, Thomas; Rommer, Paulus; Zettl, Uwe Klaus
Background: Therapeutic plasma exchange (TPE) is frequently used in glucocorticosteroid (GCS)-refractory multiple sclerosis (MS) relapses. Data regarding predictors of treatment response are scarce. The objective of this study was to analyze predictive factors for response to TPE in GCS-refractory MS patients. Methods: A total of 118 MS patients in two tertiary MS centers were analyzed. Primary outcome was TPE response defined as marked, mild, or no improvement. Secondary outcome was change in expanded disability status scale (ΔEDSS). ΔEDSS and relapse activity within 6 months after TPE were studied. Results: Marked or mild improvement was observed in 78.8% of patients. ΔEDSS correlated significantly inversely with time from relapse to start of TPE (τ = –0.239, p = 0.001), age (τ = 0.182, p = 0.009) and disease duration (τ = –0.167, p = 0.017). In multivariate analysis, TPE response was predicted by diagnosis of relapsing MS [odds ratio (OR): 3.1], gadolinum-enhancement on magnetic resonance imaging (OR 3.2), age (OR 0.5 per 5 years older) and time from relapse onset to TPE (OR 0.7 per 7 days longer). Conclusion: Patients with longer disease duration and higher EDSS pre and post-TPE were more likely to show further disability progression or relapses within 6 months after TPE. No sustained effects were observed during the follow-up period.